Analysis of Infant Mortality between 2014-2017 in Elazig - Kaya, Ferit; Pirincci, Edibe; Kaya, Medine; Selçuk, Engin Burak (My University, 2024)
Objective: In this study, it was aimed to evaluate the causes of infant mortality examined by the \"Infant Mortality Investigation Board\" in Elazig. Materials and Methods: A total of 359 cases that occurred during the four-year period between 2014-2017 were included in the study. Results: When the cases were evaluated according to the time of death, 44.8% (161) was early neonatal death, 24.0% (86) was late neonatal death, 68.8% (247) neonatal death and 31.2% (112) was determined as postneonatal infant death. By the evaluation of the main causes of death according to the case forms of the provincial board, prematurity and diseases related to prematurity ranked first with 45.2%, congenital heart diseases took the second place with 11.5%, and congenital anomalies took the third place with 9.1%. As a result; 2/3 of the infant mortality rate occurred in the neonatal period. Prematurity and diseases related to prematurity is the first leading cause of infant death. Among infant deaths, mortality rate in the neonatal period; is significantly higher in infants with low maternal education level, in not breastfed, to meconium exposed, and low birth weight cases. In addition, the rate of advanced age pregnancy and consanguineous marriage is also observed as high. Conclusion: In order to reduce the cause of death due to prematurity, measures should be taken to strengthen prenatal care, prevent advanced maternal age pregnancies and consanguineous marriages.
Keywords: Neonatal mortality; Infant mortality; maternal and child health